(untitled) (Research, Society and Development, 2017)
The History of Physics stands out as a possibility to help make teaching more critical Physics, revealing a concern to make it more efficient and more adjusted to reality. Knowing the history of physics, its development and the process of acceptance of scientific theories can help to emphasize the non-linearity of physics and the different readings that it can have, for history shows us "why" of the conceptual categories of science. The considerations of this article try to show the need for contextualized Physics in its history and the importance of the history of physics as a fundamental axis in the teaching - learning process.